Nematode parasites of two anuran species Rhinella schneideri (Bufonidae) and Scinax acuminatus (Hylidae) from Corrientes, Argentina - Hamann, Mónika Inés (2008)
The nematological fauna of most anuran species from Corrientes province, north of Argentina; has not been studied. We report for the first time the nematode species found in Rhinella schneideri and Scinax acuminatus. Forty four amphibians representing two species (R. schneideri -six males, three females and two juveniles- and S. acuminatus –fifteen males and eighteen females) were collected near the city of Corrientes, between January 2002 and December 2003 and searched for nematodes. R. schneideri contained eight species of nematodes (adults: Rhabdias füelleborni, R. elegans, Oswaldocruzia proencai, Cosmocerca podicipinus, C. parva and Falcaustra mascula; larvae: Porrocaecum sp. and Physaloptera sp.), and S. acuminatus contained three (adults: Cosmocerca parva and Oxyascaris caudacutus; larvae: Physaloptera sp.). We present morphology (scanning electron microscope) and metric information, range extensions, and new host records for these nematode species. Rev. Biol. Trop. 56 (4): 2147-2161. Epub 2008 December 12.